Primary Sjögren's Syndrome First Presenting as Hypokalemic Quadriparesis - Rolando MARTÍNEZ-GRANADOS,; Guillermo DELGADO-GARCÍA,; Martín WAH-SUÁREZ,; Nancy CONTRERAS-GARZA,; Dionicio GALARZA-DELGADO, (Archives of Rheumatology, 2017)
Hypokalemic paralysis and respiratory failure associated with distal renal tubular acidosis as first clinical manifestation of primary Sjögren's syndrome has been reported a few times. In this article, we describe the case of a previously healthy 38-year-old female patient who presented to the emergency department with a three-day history of dyspnea at rest and rapidly progressive generalized muscular weakness. Her initial work-up revealed an uncompensated hyperchloremic metabolic acidosis and severe hypokalemia. Additionally, urine pH of 8.0 and other findings consistent with distal renal tubular acidosis were found. We excluded the most common causes of distal renal tubular acidosis and finally established the diagnosis of primary Sjögren’s syndrome. Our patient was treated with potassium citrate and later discharged on this treatment.